If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x * x + -23 = 52 + -2x * x Multiply x * x x2 + -23 = 52 + -2x * x Reorder the terms: -23 + x2 = 52 + -2x * x Multiply x * x -23 + x2 = 52 + -2x2 Solving -23 + x2 = 52 + -2x2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x2' to each side of the equation. -23 + x2 + 2x2 = 52 + -2x2 + 2x2 Combine like terms: x2 + 2x2 = 3x2 -23 + 3x2 = 52 + -2x2 + 2x2 Combine like terms: -2x2 + 2x2 = 0 -23 + 3x2 = 52 + 0 -23 + 3x2 = 52 Add '23' to each side of the equation. -23 + 23 + 3x2 = 52 + 23 Combine like terms: -23 + 23 = 0 0 + 3x2 = 52 + 23 3x2 = 52 + 23 Combine like terms: 52 + 23 = 75 3x2 = 75 Divide each side by '3'. x2 = 25 Simplifying x2 = 25 Take the square root of each side: x = {-5, 5}
| 5m-4=41 | | 1/x=5-x | | 8(w-4)-5w=-17 | | 18-2x=(x-9) | | 2x+4+8x-8=180 | | ln(13/x) | | -10(s+3)=-21 | | 5x+x=510 | | -5x+xy=4 | | 2/3n=8/15 | | -(c-8)=-21 | | -4(x+2)+3=6(x+2)+2 | | x+10x+100x=11100 | | 10x+3=5x+47 | | -4v-10=46 | | 24/8=n/17 | | -7-z=-2z | | 20=2/3g | | (2-3x)(4x+5)=0 | | 7x+27=9x-7 | | 4(x+2)-10=2(x+3) | | K/9=99 | | 5+4p=6p-9 | | 8X=32/3 | | -2(6n-7n)+5n=145 | | 5(3s+8)=180 | | -4-6v=10-4r | | -3*a-6=24 | | X+27=x+77 | | a(2l+8)=80 | | -8r=-10r+10 | | Log5/7=1/3 |